Excellent Results of Revision TKA in Jehovah's Witness Patients - Harwin, Steven F.; Issa, Kimona; Naziri, Qais; Pivec, Robert; Johnson, Aaron J.; Mont, Michael A. (The Journal of Knee Surgery, 2013)
Revision total knee arthroplasty (TKA) can be quite challenging in Jehovah's Witness patients because blood transfusion is often needed, however, these patients do not accept allogeneic or autologous blood due to religious convictions. We reported our clinical experiences with a special blood management protocol for Jehovah's Witnesses who underwent a revision TKA. There were 12 self-reported Jehovah's Witness patients (12 total knee arthroplasties) who had a mean age of 69 years (range: 55 to 79 years) and who underwent revision TKA between 1998 and 2009. All revision surgeries were due to aseptic component failure. Implant survivorship was 100% over a mean follow-up of 62 months (range: 24 to 120 months). The Knee Society objective and function scores improved to a mean of 83 and 82 points, respectively. The authors believe that the use of this blood management protocol was responsible for the excellent clinical outcomes.
Keywords: total knee arthroplasty; revision; Jehovah's Witnesses; blood transfusion; clinical outcome